Study Analysis Fuel from Plastic Waste - Azharuddin; Dwi Arnoldi; Fenoria Putri; Kemas M. Fadhil Almakky; M. Ivan Davala (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2021)
The explosion of plastic-based waste (polymer) in the environment, as a result of its excessive use, so that this phenomenon causes damage to environmental ecosystems, water absorption is not optimal causes flooding, and polluting nutrients in the soil. Plastic is a polymer compound composed of the main elements, namely carbon and hydrogen. The best results in this study by using this tool have a physical appearance: yellow like premium fuel type